A systematic review of nonpharmacological prenatal interventions for pregnancy‐specific anxiety and fear of childbirth. Issue 1 (23rd October 2017) - Stoll, Kathrin; Swift, Emma Marie; Fairbrother, Nichole; Nethery, Elizabeth; Janssen, Patricia
Abstract: Background: Despite a sharp increase in the number of publications that report on treatment options for pregnancy‐specific anxiety and fear of childbirth (PSA/FoB), no systematic review of nonpharmacological prenatal interventions for PSA/FoB has been published. Our team addressed this gap, as an important first step in developing guidelines and recommendations for the treatment of women with PSA/FoB. Methods: Two databases (PubMed and Mendeley) were searched, using a combination of 42 search terms. After removing duplicates, two authors independently assessed 208 abstracts. Sixteen studies met eligibility criteria, ie, the article reported on an intervention, educational component, or treatment regime for PSA/FoB during pregnancy, and included a control group. Independent quality assessments resulted in the retention of seven studies. Results: Six of seven included studies were randomized controlled trials (RCTs) and one a quasi‐experimental study. Five studies received moderate quality ratings and two strong ratings. Five of seven studies reported significant changes in PSA/FoB, as a result of the intervention. Short individual psychotherapeutic interventions (1.5‐5 hours) delivered by midwives or obstetricians were effective for women with elevated childbirth fear. Interventions that were effective for pregnant women with a range of different fear/anxiety levels were childbirth education at the hospital (2 hours), prenatal Hatha yoga (8 weeks), and an 8‐week prenatal education course (16 hours). Conclusions: Findings from this review can inform the development of treatment approaches to support pregnant women with PSA/FoB.